A STUDY OF THE EVOLUTION AND PHYSICAL TRAITS OF TWO COMPETING STREET PATTERNS: NARROW MEANDERING AND WIDE GRIDIRON: A study about Narrow meandering street pattern and Gridiron - Yaseen, Aneela; Nida Jawad; Waqas O. Khel (Journal of Arts & Social Sciences, 2022)
A street is a passageway for people in a built environment and is one of the essential elements of urban planning. Streets convey a city's history, urban form, and socio-cultural values of societies that shape it. Street patterns must be carefully planned to create safe environments for everyone, particularly youngsters and elders. There are two common street patterns in history: meandering and gridiron. The development of these two opposed street patterns is examined in this study using historical discourse. In this study, the deductive approach is employed to distinguish between the physical traits of the street types mentioned above. According to this study, meandering street patterns reflect more concerns to human senses, socio-cultural values and aesthetics than gridiron. This research instigates further investigation in this regard to create inclusive, safe streets for everyone